Agroforestry and soil carbon sequestration: Interlinkages with soil health and climate change mitigation - Shuaib, Muhammad Bashir; Sauwa, Muhammad Murtala; Adigwe, Fidelis Atuanya; Afolabi, Ayomide Emmanuel; Musah, Mahama (International Journal of Sustainable Agricultural Research, 2025)
Agroforestry is recognized as a multifunctional land use system that provides numerous benefits, including improved soil quality, enhanced agricultural productivity, and reduced climate change impacts. This article explores the mechanisms behind the underground storage of soil organic carbon (SOC) in agroforestry systems, emphasizing its link to soil health and climate resilience. Trees contribute to SOC through processes such as the addition of organic matter from falling leaves and dying roots, which enhances carbon storage and initiates essential soil functions like humification, mineral association, and aggregate formation that protect against microbial decay. The organic matter’s quality, particularly its lignin and nitrogen content, influences decomposition rates, affecting nutrient cycling and long-term carbon stability. Research illustrates significant increases in SOC across various agroforestry practices involving crops, livestock, and trees, with tree systems demonstrating the most substantial daily carbon deposition and biological enrichment. A global synthesis indicates that even a modest increase in agroforestry (up to 30 percent) could sequester between 12 to 19 petagrams of carbon dioxide, notably in regions like South America, sub-Saharan Africa, and Southeast Asia, which exhibit high potential. Besides carbon sequestration, agroforestry positively influences soil structure, nutrient cycling, and microbial diversity, thereby promoting ecologically resilient and productive farming. However, outcomes vary by context, influenced by climate, soil properties, species diversity, and management practices. The article concludes that agroforestry is a scientifically valid natural climate solution and sustainable agriculture alternative, with its effectiveness hinging on intentional policy support and its inclusion in climate mitigation strategies.